A novel hip joint prosthesis with uni-directional articulations for reduced wear. (March 2022) - Dalli, Donald; Buhagiar, Joseph; Mollicone, Pierluigi; Schembri Wismayer, Pierre
Abstract: A novel polymer-on-metal hip joint prosthesis design that makes use of uni-directional articulations was developed and tested in this work. The new implant was tested using two polymer variants, virgin ultra-high molecular weight polyethylene (UHMWPE), and Vitamin E-infused highly crosslinked polyethylene (VEHXPE). The degrees of freedom of the ball-and-socket are reproduced by three cylindrical orthogonally-aligned articulations. This unconventional design leverages on the molecular orientation hardening mechanisms of the polyethylene and increased contact area to minimize wear. An experimental hip joint simulator was used to compare the gravimetric wear of the conventional ball-on-socket and the new implant. The new prosthesis including UHMWPE components produced a 78% reduction in wear, whereas the new prosthesis with VEHXPE components produced a 100% reduction in wear, as no measurable wear was detected. Machining marks on the acetabular cups of the new prosthesis were retained for both polyethylene variants, further demonstrating the low levels of wear exhibited by the new implants. Both polyethylene materials produced particles in the range of 0.1–1.0 μm, which are the most biologically active. Nonetheless, the extremely low wear rates are likely to induce minimal osteolysis effects. Furthermore, the novel design also offers an increase of more than 24% in the range of motion in flexion/extension when compared to a dual-mobility hip implant. A prototype of the prosthesis was implanted into a Thiel-embalmed human cadaver during a mock-surgery, which demonstrated high resistance to dislocation and the possibility of performing a figure of four position. Graphical abstract: Image 1 Highlights: ● The proposed hip prosthesis design, consisting of three orthogonal metal-on-polyethylene cylindrical articulations, produced significant lower wear than a ball-and-socket prosthesis. ● Machining marks on UHMWPE and VEHXPE cups of the new design were retained following the wear tests, indicating that minimal wear occurred. ● The cylindrical design provides a range of motion of at least 175° along the flexion/extension directions, whilst reducing the risk for dislocation.